Pre-Harvest Foliar Application Effects of Mineral Nutrients on Yield, Quality and Shelf Life of Broccoli - Tarafder, Sushanta Kumar; Biswas, Mrityunjoy; Mondal, Asit Baran (International Journal of Sustainable Agricultural Research, 2022)
This study was conducted at the farmer’s field of Jashore Sadar Upazila, Bangladesh during the Rabi seasons of 2020-2021 to evaluate pre-harvest foliar application effects of mineral nutrients on yield, quality and shelf life of broccoli. The experiment was designed in Randomized Complete Block Design (RCBD), including three replications and seven treatments for field study which were: T1=control, T2=Ca@o.30%, T3=B@o.30%), T4= Zn@o.30%, T5=Mo@o.30%, T6=Mn@o.30%, and T7= (Ca+B+Zn+Mo+Mn)@o.30%. In order to determine the shelf life of broccoli, a Completely Randomized Design (CRD) was conducted with three replications considering three factors; (i) pre-harvest foliar application of mineral nutrient sources; (ii) room temperature along with storage materials, and (iii) cold storage along with storage materials that were used accordingly. Findings revealed that the effects of pre-harvest foliar application of mineral nutrients had a significant influence on the yield, post-harvest quality, and shelf life of broccoli. The treatment T7 (Ca+B+Zn+Mo+Mn)@o.30% produced significantly in all respects of yield contributing attributes denoting curd length, diameter, and marketable curd yield of broccoli. The same treatment effectively increased post-harvest quality attributes such as color, compactness, texture, dry matter, fats, carbohydrates, energy, vitamin C, antioxidants, and phenols content in the curd. In addition, the treatment also recorded the highest shelf life of 7.25 days at room temperature (14-240c with RH 60-65%) and 24.33 days at cold storage (40c with RH 90-95%) conditions within a High-Density Polyethylene (HDP; 15 micron) Vacuum pack.